Implementation of the Indonesia–Australia Comprehensive Economic Partnership Agreement (IA-CEPA) within the International Free Trade Framework - Muhammad Akmal Cahya Fuady; Megahnanda Alidyan Kresnawati (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study examines the implementation of the Indonesia–Australia Comprehensive Economic Partnership Agreement (IA-CEPA) during the 2020–2024 period through the perspective of the Free Trade Agreement (FTA) theory. The research employs a qualitative method with a descriptive-analytical approach, drawing on secondary data from academic literature, official government reports, and bilateral trade statistics. The findings indicate that the implementation of IA-CEPA has produced positive impacts, including increased trade volume, expanded market access, and enhanced cooperation in the fields of investment and services. Nevertheless, challenges persist in the form of uneven benefits between Indonesia and Australia, non-tariff barriers, and Indonesia’s limited institutional capacity. These findings highlight that the effectiveness of an FTA is determined not only by the substance of the agreement itself but also by the domestic readiness of participating countries to manage the transition toward trade liberalization.